The Effect of Promotion, Price and Product Quality on Consumer Loyalty of PT. Palmanco Inti Sawit: The Effect of Promotion, Price and Product Quality on Consumer Loyalty of PT. Palmanco Inti Sawit - Selvy Tanashia; Wiriyanto Pangestu; Monica Monica; Namira Ufrida Rahmi (Institute of Computer Science (IOCS), 2020)
This research was carried out at PT. Palmanco Inti Sawit. This study aims to determine and analyze the effect of promotion, price and product quality on consumer loyalty at PT. Palmanco Inti Sawit. The population in this study were customers of PT. Palmanco Inti Sawit, amounting to 145 respondents and a sample of 106 respondents. The data analysis technique uses multiple linear regression analysis with the help of the SPSS program. The results showed that partially promotion has a positive and significant effect on consumer loyalty in PT. Palmanco Inti Sawit. Partially the price has a positive and significant effect on consumer loyalty at PT. Palmanco Inti Sawit. Partially product quality has a positive and significant effect on consumer loyalty at PT. Palmanco Inti Sawit. Simultaneously promotion, Price and product quality have a positive and significant effect on consumer loyalty at PT. Palmanco Inti Sawit.